2014
DOI: 10.1152/ajprenal.00251.2013
|View full text |Cite
|
Sign up to set email alerts
|

Cytochalasin E alters the cytoskeleton and decreases ENaC activity in Xenopus 2F3 cells

Abstract: Numerous reports have linked cytoskeleton-associated proteins with the regulation of epithelial Na(+) channel (ENaC) activity. The purpose of the present study was to determine the effect of actin cytoskeleton disruption by cytochalasin E on ENaC activity in Xenopus 2F3 cells. Here, we show that cytochalasin E treatment for 60 min can disrupt the integrity of the actin cytoskeleton in cultured Xenopus 2F3 cells. We show using single channel patch-clamp experiments and measurements of short-circuit current that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…Polyclonal antibodies specific for each ENaC subunit were used to immunoprecipitate ENaC and pull-down associated proteins. These antibodies were previously characterized [28] and it was demonstrated that they can be used to enrich for each specific ENaC subunit [23]. The blots were then probed for GAPDH to identify an association between ENaC subunits and GAPDH.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyclonal antibodies specific for each ENaC subunit were used to immunoprecipitate ENaC and pull-down associated proteins. These antibodies were previously characterized [28] and it was demonstrated that they can be used to enrich for each specific ENaC subunit [23]. The blots were then probed for GAPDH to identify an association between ENaC subunits and GAPDH.…”
Section: Resultsmentioning
confidence: 99%
“…ENaC interacts with several actin cytoskeleton associated proteins including MARCKS, filamin, and fodrin [19, 23, 28]. The actin cytoskeleton serves as an organizing center to keep ENaC and key regulators including other proteins and lipids in close proximity.…”
Section: Introductionmentioning
confidence: 99%
“…In a study on Xenopus cells, the treatment with cytochalasin at a concentration of 1·5 μ mol l −1 changed the shape of the cells from polygonal to flattened (Reifenberger et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…This inhibition of actin polymerization occurs because cytochalasin E binds to the ends of actin filaments and prevents their elongation and shortening (Reifenberger et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Proteins that have been shown to regulate trafficking of AQP2 to the apical plasma membrane include F-actin, Hsc70 (heat shock constitutive), and A kinase anchoring proteins (11). ENaC directly interacts with the myristoylated alaninerich C kinase substrate (12)(13)(14), filamin (13,15), 14-3-3 proteins (16)(17)(18), actin (19)(20)(21), and actin binding proteins (22,23). We recently showed ENaC activity in cultured mouse cortical collecting duct cells is regulated by exosomal GAPDH (24).…”
mentioning
confidence: 99%